Pola Pertumbuhan Ekonomi Daerah Otonomi Baru (DOB) Berdasarkan Tipologi Klassen di Provinsi Lampung - Ukhti Ciptawaty (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2019)
The abstract is written in English. The abstract contains the research objectives. The importance of regional expansion is used as one of the reasons to encourage the acceleration of economic growth in a region. In the macro analysis, the level of economic growth achieved by a country/region is measured by the development of real national income achieved by an area. Therefore, the author wants to see how the structure of economic growth in the new autonomous region after the enactment of regional expansion. So the question raised through this research is how the pattern and structure of economic growth in each DOB so that it becomes the input for the DOB concerned to increase economic growth in the area. Therefore, the purpose of this study has the main objective of finding patterns and structures of economic growth in each DOB.